Toxicities of Immunotherapy for Small Cell Lung Cancer - Fu, Yang; Zheng, Yue; Wang, Pei-Pei; Ding, Zhen-Yu (Frontiers in Oncology, 2021)
Small cell lung cancer (SCLC), composing 15-20% of lung cancer, is a fatal disease with extremely poor prognosis. In the past two decades, etoposide platinum doublet chemotherapy remained the only choice of therapy, with disappointing overall survival ≤1 year for the metastatic disease. Novel treatments including immunotherapy are urgently needed and extensively explored. Recently, in 2 phase III trials, atezolizumab and durvalumab were shown to bring survival benefit to patients. While immunotherapy brings better outcome, it is accompanied by adverse events different from traditional treatments. Although these immune-related adverse events (irAEs) are generally mild and can be managed, some irAEs (myocarditis, pneumonitis) may be severe and even life-threatening. Accompanying with the increasing application of immunotherapy in clinical practice, the irAEs should not be overlooked. In this review, the irAEs profile in clinical trials of immunotherapy for SCLC will be summarized, also its unique features compared with irAEs in other malignancies will be explored. This review may be helpful for the appropriate clinical use of immunotherapy for SCLC.